Latin American Universities: Stuck in the Twentieth Century - Knobel, Marcelo; Bernasconi, Andrés (International Higher Education, 2017)
The higher education sector in Latin America has fallen short of its promise of spearheading cultural, social, and economic progress for the region. As higher education changes to meet the challenges on the new century, the few flagship universities of Latin America are called upon to lead. However, these universities face both internal and external obstacles that hinder their full modernization, threatening their leadership.